Mechanism of Biocatalytic Friedel–Crafts Acylation by Acyltransferase from Pseudomonas protegens - Sheng, Xiang (ACS Catal, 2019)
[Image: see text] Acyltransferases isolated from Pseudomonas protegens (PpATase) and Pseudomonas fluorescens (PfATase) have recently been reported to catalyze the Friedel–Crafts acylation, providing a biological version of this classical organic reaction. These enzymes catalyze the cofactor-independent acylation of monoacetylphloroglucinol (MAPG) to diacetylphloroglucinol (DAPG) and phloroglucinol (PG) and have been demonstrated to have a wide substrate scope, making them valuable for potential applications in biocatalysis. Herein, we present a detailed reaction mechanism of PpATase on the basis of quantum chemical calculations, employing a large model of the active site. The proposed mechanism is consistent with available kinetics, mutagenesis, and structural data. The roles of various active site residues are analyzed. Very importantly, the Asp137 residue, located more than 10 Å from the substrate, is predicted to be the proton source for the protonation of the substrate in the rate-determining step. This key prediction is corroborated by site-directed mutagenesis experiments. Based on the current calculations, the regioselectivity of PpATase and its specificity toward non-natural substrates can be rationalized.